DAMPAK SERTA USAHA PEMULIHAN UMKM PASCA PANDEMI COVID-19 - Dwi Hanggoro (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
UMKM is a business activities that can expand employment, said the work area economy in the service to the public, and participate in the process and increasing the income of the equity. Pandemic COVID-19 certainly provide significant effect on domestic economy and the existence of SME. This research aims to analyze the impact of the COVID-19 pandemic on the SME’s sector in Indonesia as well as the efforts made by the SME’s the COVID-19 to handle this pandemic situation. The research method used in qualitative descriptive research, data collection techniques using documentation techniques, namely collecting data from various reference source. The result showed that COVID-19 pandemic would make the impact of the decline in income but was also found that there are measures which have been taken by the business. So it can be said that your COVID-19 pandemic caused a decline in performance.